(3abg GdbQBfs - (3SYjO Hf gHI Gddg Hf GdMSf GdQGhfOqj, CHh GdMSf, bWH GdOjf,J (B573 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdPi Medfi Ydi GdTQhY ai LeY gPG GdcJGH s
(3BNQgG (B:s
(3EfeG TQW ai GdBjI Hbhdg GdPjf ef CUdGHce dFdG jJhge Cf GdOYi EP CJjfGg CHhg MQe Ydjg fcGM RhLJg s
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B233s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis